The treasure house - Khan, Saniyasnain; Sarkar, Ramendranath (Goodword Kidz New Delhi, India, 2003)
The Treasure House from the Quran Stories for Little Hearts series tells the story of Qarun (Korah) and his immense wealth, illustrating the consequences of arrogance and greed. Through simple, child-friendly narration, it teaches young readers the value of humility and gratitude in the eyes of God.